Murder in the archives: The case of Valentine Shortis (pt. 1/2) - Sivakumaran, Elakkiya (Special Collections & Archives, University of Waterloo Libraries, 2017)
Back in November, I began reading The Complete Tales of Sherlock Holmes by Arthur Conan Doyle, and although I’m not the biggest fan, it came in handy with this. No, it didn’t inspire me to write about everyone’s favourite cocaine addict, but it did remind me that when it comes to murder stories, I much prefer nonfiction to fiction, which prompted me to look for other murder-related books in our catalogue.
Keywords: SCA blog; Valentine Shortis; Crime--Canada--History; Martin Friedland